Substrate-controlled selectivity switch in the three-component coupling involving arynes, aromatic tertiary amines, and CO2 - Bhojgude, Sachin Suresh; Roy, Tony; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2016)
The transition-metal-free multicomponent coupling involving arynes, aromatic tertiary amines, and CO2 is reported. The reaction exhibits switchable selectivity depending on the electronic nature of the aromatic amines used. With amines bearing electron-releasing/neutral groups as the nucleophilic trigger, the reaction afforded 2-arylamino benzoates via a nitrogen to oxygen alkyl group migration. Employing electron-deficient amines in the reaction furnished 2-aminoaryl benzoates proceeding via the aryl to aryl amino group migration resembling a Smiles rearrangement.